2014
DOI: 10.1302/0301-620x.96b11.34452
|View full text |Cite
|
Sign up to set email alerts
|

The revision acetabulum – allograft and bone substitutes

Abstract: A common situation presenting to the orthopaedic surgeon today is a worn acetabular liner with substantial acetabular and pelvic osteolysis. The surgeon has many options for dealing with osteolytic defects. These include allograft, calcium based substitutes, demineralised bone matrix, or combinations of these options with or without addition of platelet rich plasma. To date there are no clinical studies to determine the efficacy of using bone-stimulating materials in osteolytic defects at the time of revision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Previous in vitro investigations showed that leukocyte- and platelet-rich plasma (L-PRP) gel is active against selected bacterial strains [ 6 8 ]. Some authors also reported clinical observations about a decreasing number of infections and the induction of healing processes after L-PRP use in orthopedics [ 9 ], trauma [ 10 ], maxillofacial [ 11 ], and cardiac surgery [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro investigations showed that leukocyte- and platelet-rich plasma (L-PRP) gel is active against selected bacterial strains [ 6 8 ]. Some authors also reported clinical observations about a decreasing number of infections and the induction of healing processes after L-PRP use in orthopedics [ 9 ], trauma [ 10 ], maxillofacial [ 11 ], and cardiac surgery [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many formulations, such as ProOsteon, Osteoset (calcium sulfate ceramic), and Vitoss (tricalcium phosphate scaffold), are available; although they may be effective at least in the short term for smaller lesions, the efficacy of these materials is still largely unknown. 46 In addition, concerns exist that if this material migrated into the joint space, it could lead to third-body wear. 47 Stamenkov et al 35 used highresolution CT to follow up 22 osteolytic lesions in six patients over approximately 4 years.…”
Section: Clinical Outcomes Of Reconstructive Optionsmentioning
confidence: 99%
“…Sin embargo, los resultados en el uso de aloinjerto han sido variables respecto a su integración, y el subsecuente aflojamiento. 25,26 El uso de copas jumbo con cuñas metálicas para la solución de defectos osteolíticos acetabulares es actualmente la forma de revisión más empleada por cirujanos de cadera en cirugía ATC de revisión. 27 Los resultados han sido más constantes, eliminando el riesgo de reabsorción ósea en injertos y disminuyendo el riesgo de aflojamiento o falla en implantes con tasas de supervivencia de copas revisión de más de 90 a 95% a cinco años en diferentes series.…”
Section: Wwwmedigraphicorgmxunclassified